The Level of Anxiety of Pregnant Women and Postpartum Mothers During the Covid-19 Pandemic in Kejapan Sub-District - Aprilya Tunggo Dewi; Ety Diana Sulistyawati (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
COVID-19 has an impact on people's welfare, it can be a psychological problem for pregnant women and postpartum mothers, one of which is anxiety. The purpose of this study was to determine the picture of the anxiety level of pregnant women and postpartum mothers during the COVID-19 pandemic. Research design is descriptive research. The samples were 28 pregnant women and 23 postpartum mothers in Kejapanan sub-district using cluster sampling technique. The instrument used is the perinatal anxiety screening scale (PASS). The results obtained were pregnant women and postpartum mothers in Kecmatan Kejapanan, during the COVID-19 pandemic, the majority experienced anxiety on a mild-moderate scale.